South of the border: some notes about the democracy in the Iberian America - Vouga, Cláudio (FCL-UNESP Laboratório Editorial, 2007)
This paper presents the reasons why the political democracy in the Iberian American countries is under threat or in a deep crisis and why the popular masses seem to face these challenges with indifference. The argument is that democracy has to fit in the situation or the context and that the North American model of democracy should be substituted by the democracy of the Iberian people.